Molecular characterization of Chrysaora cf. caliparea (Scyphozoa: Semaeostomeae: Pelagiidae) from the coast of Qatar - Boughattas, Sonia; Mushtaha, Mohanad; Yahia, Mohamed Nejib Daly; Albatesh, Dana; Althani, Asmaa A.; Benslimane, Fatiha M. (Zootaxa, 2026)
The jellyfish Chrysaora cf. caliparea was recently reported as the first Scyphomedusae record for Qatar based on morphological affinity, though genetic confirmation was lacking. To definitively substantiate its taxonomic identity, we conducted hereby a molecular analysis. Specimens were collected (n=3), subjected to DNA extraction, PCR amplification and sequencing targeting 16S, 28S and COX genes. The Maximum Likelihood phylogenetic analysis advanced that the Qatari specimen likely represents either a previously unidentified species or the genuine Chrysaora cf. caliparea. Considering the morphological and biometric analysis of an adult population (n=94) presented in the current study, in addition to the genetic data, we could attribute the identity of the Chrysaora specimens in the Arabian Gulf to Chrysaora cf. caliparea. Our integrative approach combining morphological and molecular data can serve as a framework for delineating species diversity across challenging taxonomic groups.